Impact of Monsoon Rainfall on Roadside Slopes - Adhikari, Laxmi; Bhatt, Jayant; Thapa, Shreejan Bikram; Maharjan, Lipika; Dahal, Kushal; Rimal, Madan; Timilsina, Prajwal; Dahal, Bhim Kumar (Journal of Engineering Technology and Planning, 2025)
Monsoon-induced landslides pose a severe threat to Nepal’s hilly and mountainous regions, frequently causing highway disruptions and substantial loss of life and property every year. This study examines a 4 km section of the Dakshinkali-Kulekhani road to assess the effects of monsoon rainfall on roadside slope stability. Field data, including slope geometry, land use, and the presence and condition of erosion control measures (ECM), were recorded before and after the monsoon, alongside photographic documentation at each chainage of the study route. Rainfall data were collected for the study area, and soil samples from failed sections underwent laboratory tests to determine relevant index and engineering properties. Slope stability analysis combined with transient seepage modeling was performed using GeoStudio on key sections with slope failures. Among 188 sections under considerations, 62 experienced significant slope failures, predominantly in areas lacking effective ECM; even where ECM existed, they were often insufficient and showed considerable collapse post-monsoon. Most of the failures occurred on slopes excavated on soft rocks. A strong inverse relationship was observed between rainfall intensity and factor of safety, with four critical high-rainfall days causing rapid declines in factor of safety through rainwater infiltration. This study underscores the urgent need for improved and site-specific slope protection strategies to mitigate landslide risks under intense monsoon conditions in Nepal’s mountainous terrain.